Contributions of team climate in the study of interprofessional collaboration: a conceptual analysis - Bailey, Christopher; Agreli, Heloise F.; Peduzzi, Marina (Taylor & Francis, 2017)
The concept of team climate is widely used to understand and evaluate working environments. It shares some important features with Interprofessional Collaboration (IPC). The four-factor theory of climate for work group innovation, which underpins team climate, could provide a better basis for understanding both teamwork and IPC. This article examines in detail the common ground between team climate and IPC, and assesses the relevance of team climate as a theoretical approach to understanding IPC. There are important potential areas of overlap between team climate and IPC that we have grouped under four headings: (1) interaction and communication between team members; (2) common objectives around which collective work is organised; (3) responsibility for performing work to a high standard; and (4) promoting innovation in working practices. These overlapping areas suggest common characteristics that could provide elements of a framework for considering the contribution of team climate to collaborative working, both from a conceptual perspective and, potentially, in operational terms as, for example, a diagnostic tool.